Translators’ Personality in the Translations of D.O. Fagunwa’s Igbó Olódùmarè - Clement Odoje (Yoruba Studies Review)
The concept “Translation” has been examined by many scholars from different perspectives, but little attention has been devoted to the personalities of the translators in their translation works. The concern of this essay is to consider the personalities of the translators of D.O. Fagunwa’s novel, Igbó Olódùmarè in line with the theories of Natural and Directional equivalence to foreground the idea that translation is heavily dependent on the translators’ personality. It was found that translators’ motive, purpose, language choice, and religious background have an immense influence on their approach to translation.